Комп’ютерний моніторинг вітропотенціалу: концептуальний підхід, система відбору параметрів вітрового потоку - Дудикевич, Б. В.; Микитин, Г. В.; Опірський, І. Р.; Пащук, О. В.; Dudykevych, V.; Mykytyn, H.; Opirskyy, I.; Pashuk, O. (Видавництво Львівської політехніки, 2018)
Висвітлено системне бачення контролю параметрів вітрового потоку, яке на основі концептуального підходу до створення комп’ютерного моніторингу параметрів вітру та системи реєстрації даних дає змогу відображати отримані результати в режимі реального часу, що забезпечує достовірність інформації та прискорює прийняття рішень щодо розгортання вітроенергетичних станцій (ВЕС) та вибору типу вітротурбінних генераторів (ВТГ). Запропоновано концептуальний підхід до створення комп’ютерного моніторингу параметрів вітрового потоку на основі інформаційної програми моніторингу сили вітру та методології оцінювання зареєстрованого вітропотенціалу. Розроблено комп’ютерну систему реєстрації вітрового потоку, що забезпечує можливість здійснювати відбір, обробку та передавання даних про параметри вітру та оцінювати вітропотенціал і приймати управлінські рішення щодо встановлення ВЕС та вибору типу ВТГ.

Conceptual approach to study of wind flow parameters computer monitoring has been created on the basis of the appropriate information program and the methodology for assessing the wind power. Structure of the monitoring program covers: the purpose and tasks of monitoring the parameters of the wind flow, e.g. the speed and direction of the wind for the certain period in accordance with the chosen site for the establishment of meteopost in obedience to the optimal criteria of wind energy efficiency. The methodology includes: a method for registering a wind stream, based on the choice of the method of automated registration and the creation of a computer control system for wind flow at the site of the region. The method of data registration is the location of the sensor-anemometer and weathervane at a height of 27 meters, which is due to the location of the bottom of the wheel turbine generator at a given height and the transfer of the data to the server. Experimental data from meteoposts are processed, recorded for further visualization in the form of graphs of velocity and wind direction and the construction of the winds of rocks, which is a criterion for determining the optimal location of generators. According to the determined wind power potential, the choice of type of wind turbine generators is substantiated. The developed computer monitoring system of wind streams is designed for accurate analysis of the wind power of the area and detailed testing of available mathematical models of wind turbine generators. The visualization spectra of the change in wind velocity and the changes in the direction of the wind flow give an integral representation of the wind power in the area and serve as the source vector for forecasting the generation of electricity from wind power. The computerized system for selecting the parameters of the wind in the proposed area with great precision and resolution in time is the basis for accurately predicting the practical feasibility of installing wind power stations in the regions of Ukraine.
Computer monitoring ofwind potential: conceptual approach, selection system ofwind flow parameters
Keywords: вітроенергетичні станції; вітротурбінні генератори; комп’ютерний моніторинг; параметри вітрового потоку; система реєстрації параметрів вітру; прогнозування вітропотенціалу; Wind Power Stations; Wind Turbine Generators; Monitoring; Flow Parameters; Registration System; Wind Power Forecasting